Pengaruh Tata Kelola Perusahaan yang Baik terhadap Kinerja Keuangan dengan Pengungkapan Laporan Berkelanjutan sebagai Variabel Moderasi - Hakim, Rizal Ziddan; Fitriasari, Rizka (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This quantitative study aims to analyze the influence of corporate governance on the financial performance of energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period, with sustainability report disclosure as a moderating variable. Corporate governance in this study is represented by managerial ownership, institutional ownership, and audit committee size. Secondary data were analyzed using multiple linear regression and moderated regression analysis to examine the moderating role of sustainability report disclosure in the relationship between corporate governance and financial performance. The results indicate that institutional ownership has a significant influence on financial performance, while managerial ownership and audit committee size do not show a significant effect. Furthermore, sustainability report disclosure significantly moderates the relationship between institutional ownership and financial performance, but does not moderate the influence of managerial ownership and audit committee size.